Using Social Interactive Writing for English Language Learners (SWELL) with Fairy Tales Videos in Teaching Writing - Rasmi Rami Rasmi (EDUVELOP, 2018)
This research aims to investigate whether the use of SWELL method with fairy tale videos improves the students’ writing ability and to find out which writing components mostly affected by the use of SWELL method. This research was conducted using a quasi-experimental design. The population of the research was the second grade students of SMPN 5 Marioriawa in academic year 2015/2016 which consisted of two classes (56 students). The sample was drawn using cluster random technique. The number of students in the class was 28 students. The research instrument used was writing test. The data obtained through the test were analyzed quantitatively by using 21.0 version of SPSS program. Based on the data analysis, the research findings reveals that there is a significant differentce of the students’ writing skill after being taught by using SWELL method. It is proved by the data that had been processed through SPSS program. The result showed that the mean score of students in experimental group was greater than the mean score in control group (85.03>67.180, with t-test value is lower than the probability value (0.000<0.05). It indicates that there is a significant improvement of students’ writing ability after the treatment. The writing skill of the second grade students of SMPN 5 Maroriawa can be improved significantly by using SWELL method with fairy tale videos. For the writing components that mostly affected by SWELL method. For different aspects of writing, content, organization, vocabulary, language use and mechanic, vocabulary is the most affected by the use SWELL method. The highest score in term of vocabulary was 18 with the percentage 90 with the highest converted score 87.55 categorized as very good categorization.